The effectiveness of low-calorie dietary interventions in managing obesity in patients. A review - Ekaterina A. Troshina; Ksenia A. Komshilova; Natalia V. Silina; Ekaterina V. Ershova; Fatima K. Dzgoeva (ZAO "Consilium Medicum", 2024)
Obesity is a complex condition that is associated with various metabolic disorders and has a significant social impact. Weight loss is primarily achieved through dietary changes, such as reducing calorie intake. Therefore, it is essential to provide patients with effective weight loss programs and recommend a low-calorie diet as soon as possible. In addition to drug therapy for metabolic disorders, it is crucial to educate patients about the importance of a healthy diet and encourage them to adopt a low-calorie approach. Numerous studies have demonstrated the effectiveness of low-calorie and very low-calorie diets for treating obesity. However, compliance with these diets can be challenging, as they require careful attention to nutritional value and the balance of macronutrients and micronutrients. Prolonged adherence to reduced dietary regimens can lead to hypovitaminosis, lack of dietary fiber, or decreased protein intake. In 2024, a new product for balanced low-calorie nutrition, OPTIFAST, was introduced on the Russian market by the Nestlé Health Science company in Germany. This product provides patients with all essential nutrients and allows them to manage their daily calorie intake. It also provides a feeling of fullness that is essential for maintaining adherence to a low-calorie diet and ensuring effective and safe weight loss, primarily through adipose tissue reduction.